WAYFINDING SEBAGAI MEDIA PENUNJANG DESTINATION BRANDING KAMPUNG KREATIF DAGO POJOK - Febriani, Gadis (Institut Bisnis dan Teknologi Indonesia, 2022)
Kampung Kreatif Dago Pojok (KKDP) as a tourism destination has a strong brand identity. Its concept is a tourist village in Bandung which appointed by UNESCO as one of Creative City. It has lots of potential for creative products and cultural activities for the tourist to experience, but minimal public communication and lack of information make the tourist miss the full experience. Using the Qualitative approach by using three steps of Design Thinking methods (Inspiration, Ideation, dan Implementation) to dig the underlying problems of this area and to propose better problem solving by utilizing the community potential and strength. Proposed Area Map and wayfinding of KKDP area as an answer to information the tourist needed. It will be applied on the wall and streets of the village and blend well with a surrounding area filled with street arts and murals. The Maps and wayfinding gave information on tourist locations and KKDP each area’s unique experiences. Each area has different products to sell and activities to do, on the maps grouped by different color so tourists can just glance and choose which experience they want. The design of the area mapping and wayfinding made in this paper acts as a design guide and the application will be done by the hand of the youngster in the community to harness their talent and potential. Hopefully, this paper will modestly contribute to the improvement of wayfinding design in the scope of tourism and destination branding.